Why Do Bidder CEOs Get Disciplined Following Mergers? - Soegiharto Soegiharto (The Indonesian Journal of Accounting Research, 2013)
This study examines the effect of CEOs' behavior (overconfidence/ less overconfidence), merger period (in-wave/non-wave), method of payment (stock/cash), industry of merged firm (across-industry/ within-industry), premium paid to target firm, and operating performance on the likelihood of a CEO turnover amongst bidding firms. Testing the US successful merger and acquisition data for the period of the 1990s, this study finds that the effect of merger waves and the method of    payment on CEO turnover are positive and significant. Three measures of CEO behavior proposed and tested in this study, however, generally have insignificant effect on CEO turnover.